2020
DOI: 10.2967/jnmt.119.229500
|View full text |Cite
|
Sign up to set email alerts
|

Lower Radiation Dosing in Cardiac CT Angiography: The CONVERGE Registry

Abstract: Coronary artery disease is the leading cause of morbidity and mortality. Tools have been developed to accurately diagnose and evaluate coronary artery disease. Coronary CT angiography (CCTA) provides detailed imaging to deliver precise analysis and prognostic information. We sought to compare the radiation dose from a 256-detector-row CT scanner with that from a 64-detector-row CT scanner across a similar profile of patients. Methods: Consecutive patients were screened for the Converge Registry study and, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The CONVERGE study compared groups of 110 patients using 64-slice and 256slice cameras in each group. The determined mean DLP values in the group tested using the 256-slice instrument (Revolution CT, GE Healthcare) were 113.5 ± 53.6 3 mGy*cm (1.59 ± 0.75 mSv) and were 32% lower than the group tested using the 64-slice instrument for the patients with normal BMI values (18.5-24.9) [56].…”
Section: Multi-slice Dual-source and Wide-field Tomographymentioning
confidence: 81%
“…The CONVERGE study compared groups of 110 patients using 64-slice and 256slice cameras in each group. The determined mean DLP values in the group tested using the 256-slice instrument (Revolution CT, GE Healthcare) were 113.5 ± 53.6 3 mGy*cm (1.59 ± 0.75 mSv) and were 32% lower than the group tested using the 64-slice instrument for the patients with normal BMI values (18.5-24.9) [56].…”
Section: Multi-slice Dual-source and Wide-field Tomographymentioning
confidence: 81%
“…As mentioned above, better delimitation of the scan range is not the only way to reduce radiation exposure [ 28 30 ]. Hausleiter et al identified several factors influencing the radiation dose in CCTAs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, detailed plaque burden quantification and characterisation, though use of automated and semi-automated software, is still time-consuming, and hardly implemented in daily routine. However, thanks to technical developments, radiation exposure has been dramatically reduced, from 5-6 mSv to an average of 1-2 mSv [78], and overestimation of vessel stenoses, mainly due to calcific burden, has been reduced [79].…”
Section: Cardiac Computed Tomography Angiography and Plaque Imagingmentioning
confidence: 99%